Cryptoassets: Legal categorization of cryptoassets and introduction to the technology DLT/Blockchain - Reinhart Schuller, Robert (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Cryptoassets have emerged in recent years as something very attractive among the population, but at the same time it has been a real headache for the legislator and also for differents countries of the world. The novelty and cross-border importance forces us to go to different regulatory projects, recommendations of authorities, as well as comparative doctrine. In the present work, the difficult challenge of fitting cryptoassets into the Spanish legal system is faced, without prejudice to proposing a series of improvements or suggestions at a European level. To face the challenge with security and certainty, it will be necessary to glimpse the technological bases of blockchain, also known as DLT.
Keywords: blockchain; DLT; cryptoassets; goods; tokens